Development of Problem Based e-Worksheet to Enhance Mathematics’ Communication Skill in Cartesian Coordinates - Wulandari, Fina; Andriyani, Andriyani (Jurnal Pendidikan MIPA, 2022)
The importance of mathematics communication as one skill in the mathematics learning process standard doesn't necessarily make learning oriented towards achieving this skill. This study aims to develop a problem-based e-worksheet and determine its validity, practicality, and effectiveness in enhancing the mathematics communication skill in the cartesian coordinate topics. This study is a Research and development using the ADDIE model containing stages of analysis, design, development, implementation, and evaluation. The results showed that the e-worksheet was declared feasible. The validity of the e-worksheet is indicated by the average score of the material and media validators which is a very good criterion. The response questionnaire average value also shows the practicality of this e-worksheet. While the effectiveness is shown by increasing students' mathematics communication skills after being given an e-worksheet. Several features of the e-worksheet and the loaded Problem-Based Learning model syntax support the effectiveness of the e-worksheet. Keywords: mathematics communication, e-worksheet, problem based learning. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp569-584